(3GdJObjb GdOGNdj Hjf hGdfXQjI hGdJWHjb habG deYGjjQ GdJObjb GdOGNdj GdOhdjIs - (3Nda YHO Gddg(B, (3GdhQOGJs ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2006)
(3eONd ddJObjb GdOGNdj,GdEWGQ GdfXQj ddJObjb GdOGNdj,GdQbGHI GdOGNdjI,GdeeGQSI GdYedjIddJObjb GdOGNdj,JbfjGJ GdJObjb GdOGNdj,GOGQI OGFQI GdJObjb GdOGNdj,GdJObjb GdOGNdj hcJGHI GdJbGQjQ,JObjb GdYedjGJ(B((3GdJObjb GdJTZjdj(B)(3,GdJObjb aj GdLgGR GdMchejs
(3GdedGMb(B:(3U(B.447-453(3; HHdjhZQGajG(B:488-490s
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs